(untitled) (European Journal of Education and Psychology, 2019)
The aim of this study was to analyze the relationship between sociometric types, behavioral categories and use of learning strategies and study skills (Attitude, Motivation, Time Management, Anxiety, Concentration, Information Processing, Selecting Main Ideas, Aid Study Scale and Self-Assessment Strategies Scale) in a sample of 1349 (51.7% boys) Spanish adolescents, ranging in age from 12 to 16 years. Methodology: the students’ sociometric nomination was performed by the Programa Socio and for the analysis of learning strategies and study, the Learning and Skills Inventory Studies High School Version, (LASSI-HS, Weinstein and Palmer, 1990) was administered. Results show that students positively nominated by their peers obtained significantly higher scores on the use of learning strategies and study skills adaptive for learning. Sociometric types were found to be a significant predictor of the use of various learning strategies and study skills, as students positively nominated by their peers were more likely to achieve high scores on the use of appropriate learning strategies to study. These findings are discussed taking into account the effect size of the differences and their theoretical and practical implication.